Educação a distância e formação docente no Sudoeste do Paraná: o protagonismo do Curso de Pedagogia - Almeron, Andrews Alves (2021)
This research is inserted in research line 1 “Culture, Educational Processes and Teacher Education” of the Stricto Sensu Post Graduation Program in Education – Master's Degree – from the Western Paraná State University (UNIOESTE), campus of Francisco Beltrão. The thematic focus on teacher training and its investigative object is the expansion of Distance Pedagogy Courses in the Southwestern of Paraná. The proposal follows the discussions and researches made by the Research Group called ” Higher Education, Academic Training and Teaching Work” (GESFORT), of wich the researcher is part of, in addition to the experiences lived through the Pedagogy Course that this institution offers and the need of understanding the thematic in face of the present conjuncture of protagonism of this modality, particularly in the licentiate courses, where Pedagogy Course is pointed out as the biggest upward. Therefore, the research problem delimits itself to answer the question: what are the implications of the expansion of distance education to the initial shaping in Pedagogy Courses in the Southwestern region of Paraná? Considering the questioning, the general goal of this reseach is to analyze the expansion of distance Pedagogy Courses in the Southwestern of Paraná, making explicit the implications to the teachers initial learning. For this purpose, the chosen methodological procedures ally the bibliographic research to a document analysis, resorting to decrees, ordinance and resolutions that relate to distance education (EaD) and to others educational policies, as well as official studies disclosed by The National Institute for Educational Studies and Research Anísio Teixeira (INEP) and by The Paraná Institute for Economical and Social Development (IPARDES). The research is sustained by a Criticial-Dialectic approach, using of a theoretical framework that made possible to analyze the object by establishing a relationship between education and society. Authors such as Schaff (1995), Belloni (1998), Preti (2011), Dardot e Laval (2016) contributed to expose the current information and communication age, articulating the EaD phenomenon since its arrival in Brazil to the relations with a hegemonic social model, besides of Gatti and Barreto (2009), Freitas (2002), Saviani (2007, 2008, 2010), Contreras (2002), on which are substantiate the studies concerning the policies of teacher education. The analysis take us to the understanding that the educational policies were responsible to secure, outline and expand the EaD in Brazil, especially with the enactment of the Law of Lines of Direction and Bases of National Education (LDBEN) number 9394/1996 and with the decree number 9057/2017. The results point the contradictions existing in this educational modality such as in the absence of philosophical foundations that guides the Distance Pedagogy Course, as well as the inaccuracies on the statistic data. Regarding the implications to the teachers learning the proletarianization of the teachers work, the teacher/student relationship and the dismantling of teacher education stood out